Photochemistry of methyl hypobromite (CH3OBr): excited states and photoabsorption spectrum. Issue 117 (11th November 2015) - Stojanović, Ljiljana; Rodrigues, Gessenildo Pereira; Aziz, Saadullah G.; Hilal, Rifaat H.; Barbatti, Mario
Abstract : From photoabsorption to photodissociation, from MRCI to TDDFT; a comprehensive benchmark on the photochemistry of methyl hypobromite (CH3 OBr) is provided. Abstract : The singlet and triplet excited states of CH3 OBr with excitation energies up to ∼9.5 eV are studied using the multi-reference configuration interaction with singles and doubles method (MRCI-SD) and several single-reference methods, including time-dependent density functional theory (TD-DFT), coupled-cluster (linear-response CC2 and equation-of-motion CCSD and CCSD(T)), and algebraic diagrammatic construction (ADC(2)). Among the single-reference methods, coupled-cluster gives vertical excitation energies and oscillator strengths comparable to the MRCI-SD values for the majority of excited states. The absorption cross section in the gas phase in the region between 2 and 8.5 eV was simulated with CCSD using the nuclear ensemble approach. The computed spectrum predicts two intense absorption bands. The first band, peaked at ∼7.0 eV, is induced by Rydberg excitation. The second band has a strong overlap between a broad σσ* transition and three Rydberg transitions, resulting in two peaks at 7.7 and 7.9 eV. The spectrum also features a low-intensity band peaking at ∼4.6 eV due to n σ* excitation. The intensity of this band is influenced by spin–orbit coupling effects. We analyzed the dissociation pathways along the O–Br and C–O coordinates by computing rigid potential energy curves of the ground and the lowest-lying singlet and triplet excited states, and discussed the possible dissociation products. Due to the specific electronic structure of the excited states, characterized by multireference, double excitations, and Rydberg states occurring in the low-energy region, their correct description along dissociation coordinates is feasible only with MRCI-SD.